MENEJEMEN PENDIDIKAN ISLAM DALAM PERSEFEKTIF AL QUR’AN DAN HADIST - Sofyan Yahya; Sartaman; Nasrudin Harahap; Nurul Hidayati Murtafiah (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2021)
Al-Qur'an and Hadith are the main sources of Islamic teachings which contain the principles of muamalah and some special rules regarding various aspects of life. Today's Muslims, especially those who adhere to Islamic law, , want whatever is learned and implemented in life to always be oriented towards the Qur'an and hadith. Al-Qurulkarim as the holy book of the Muslims, among others, functions as a